The Concepts of Japanese and German Primary School Children Relating to the Topic of Death in the Context of Values Education and the Ethics of Care – A German-Japanese Comparison with Gender Analysis - Marsal, Eva; Dobashi, Takara (ETHICS IN PROGRESS, 2011)
Our contribute compares the concepts of Japanese and German primary school children relating to the topic of death, healing in the context of values education and the ethics of care. This is a project of the German-Japanese Research Initiative on Philosophizing with Children (DJFPK), cialis 40mg which aims to facilitate individual autonomy by enhancing philosophical-ethical judgment. It encourages the application and appropriate transfer of values based on philosophical-ethical knowledge and acquired through independent reflection to the situations of daily life.